Application of artificial intelligence and automation in engineering education - Ruziev, Oybek (MMIT Proceedings, 2025)
This article analyzes the integration of artificial intelligence (AI) and automation technologies into engineering education. The advantages of using AI systems in the educational process, their influence on modern teaching methods, and ways to enhance students' potential using these technologies are considered. The role of teachers and the need for professional development are also highlighted.